Nonlinear impact of minimum wage on labor employment in China - LYU Junhan; Zhai Tianle; Peng Zicheng; Huang Xuhang (Nonlinear Engineering)
This study examines the impact of increasing minimum wages, focusing primarily on their effect on employment. Our research involved analyzing the statistics of panel data, testing fixed effects and stationary, conducting linear regression, and integrating the linear regression model with nonlinear model analysis. The results indicate that fluctuations in the employment rate are almost entirely explained by the selected explanatory variables, and there is a significant negative correlation between minimum wages and the employment rate. This study contributes to current research by providing more comprehensive analyses, particularly through the use of nonlinear models, resulting in better-fitting models. We employed multiple fitting methods for time series data and their differentials, combining these results with nonlinear analysis.